Intention to Participate in Group Prenatal Care: Moving Beyond Yes or No. Issue 1 (January 2020) - Berman, Rebecca; Weber Yorga, Kim; Sheeder, Jeanelle
Group prenatal care (GPNC) is an alternative model to traditional individual care and may improve public health outcomes. Prior studies suggest that interest in GPNC varies widely and few studies have examined characteristics predictive of interest in this model. The purpose of this study was to inform GPNC recruitment efforts by examining likelihood of participation delineated by characteristics and GPNC perceptions. Pregnant participants received information about GPNC then completed a survey measuring demographic, psychosocial, and reproductive characteristics, likelihood to participate in GPNC, and factors influencing selections. Respondents expressed varied levels of likelihood to participate in GPNC; 16.2% low likelihood, 44.9% moderate likelihood, and 38.9% high likelihood. Characteristics were similar between groups, and thus their use is not recommended when targeting recruitment efforts. Benefits outweighed barriers and threats for the high likelihood category, barriers and threats outweighed benefits for the low likelihood category, and benefits, barriers, and threats were balanced for the moderate likelihood category. Accurately assessing likelihood of participating in GPNC efficiently identifies individuals who are clearly either going to decline or participate, as well as promotes targeted recruitment efforts directed at those who are ambivalent. Understanding and addressing perceived benefits, barriers, and threats supports effective GPNC recruitment.